Information theory, evolutionary innovations and evolvability - Wagner, Andreas (Philos Trans R Soc Lond B Biol Sci, 2017)
How difficult is it to ‘discover’ an evolutionary adaptation or innovation? I here suggest that information theory, in combination with high-throughput DNA sequencing, can help answer this question by quantifying a new phenotype's information content. I apply this framework to compute the phenotypic information associated with novel gene regulation and with the ability to use novel carbon sources. The framework can also help quantify how DNA duplications affect evolvability, estimate the complexity of phenotypes and clarify the meaning of ‘progress’ in Darwinian evolution. This article is part of the themed issue ‘Process and pattern in innovations from cells to societies’.